Modeling present and future flows in a tailings pile at the former Le Cellier uranium mine (France) - Pierre L’Hermite; Anne Jost; Valérie Plagnes; Yifan Wang; Isabelle Blanc-Potard; Damien Regnier; Michael Descostes (Journal of Hydrology: Regional Studies)
Study region: The former uranium mine near Le Cellier, France represents an opportunity to investigate unsaturated flow in real conditions through a tailings pile resulting from heap leaching. Sustainable water management requires the understanding of its flows, to limit chemical reactions and avoid the migration of contaminants into the environment. Study focus: Daily monitoring of drain discharge and monthly monitoring of physicochemical parameters at the pile outlet provide reliable information on how fast the pile reacts to precipitation. A two-dimensional dual-porosity model was developed with HYDRUS 2D at a daily time step. The model integrates a simple representation of material heterogeneity, based on a sieve analysis, and the vegetation transpiration due to the presence of bushes and coniferous trees on the surface of the pile. Climate change may affect the recharge and discharge over the next 100 years with median annual discharge varying between +4.4 % and −12 % depending on greenhouse gas emission scenarios. New hydrological insights of the region: : The calibrated model correctly simulates water discharge at the pile outlet and allows its simulation under climate change. Discharge simulations show that effluents generated during events below the 200-year return period rainfall events could be stored in a buffer basin to avoid any environmental contamination. These simulations are essential to ensure sustainable future water management at this former mining site.